1990
DOI: 10.1016/0735-1097(90)90638-6
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of verapamil and procainamide on rate-dependent bundle branch block: Pharmacologic evidence for the role of depressed sodium channel responses

Abstract: The mechanisms responsible for intermittent bundle branch block are still under debate. The role of the time-dependent behavior of the slow calcium channel has recently been emphasized. To test this hypothesis and ascertain the possible involvement of the fast sodium channel, the effects of the slow calcium channel blocker verapamil and the fast sodium channel blocker procainamide were compared in 10 patients with intermittent bundle branch block. All 10 patients showed bundle branch block during spontaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, Chiale et al (Chiale, et al, 1990) studied effects of procainamide on rate-dependent bundle branch block, and concluded that clinical intermittent bundle branch block was related to depressed fast responses and not to slow calcium mediated responses. Previous experimental data on overdrive suppression of conduction in canine His-Purkinje system (Takahashi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chiale et al (Chiale, et al, 1990) studied effects of procainamide on rate-dependent bundle branch block, and concluded that clinical intermittent bundle branch block was related to depressed fast responses and not to slow calcium mediated responses. Previous experimental data on overdrive suppression of conduction in canine His-Purkinje system (Takahashi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular studies were carried out on the pharmacodynamics of antiarrhythmic drugs. 39 , 40 , 41 , 42 In vitro studies with microelectrode technique in normal and abnormal human myocardial tissues obtained from explanted hearts were performed. 43 Two original contributions were related to Brugada syndrome with reference to its etiopathogenesis and diagnosis.…”
Section: Latest Contributionsmentioning
confidence: 99%